STRUKTUR KALIMAT BAHASA ARAB DAN BAHASA PERSIA - Siti Fatimah; M. Agus Budianto (Universitas Ahmad Dahlan, 2020)
This paper describes the differences between Arabic and Persian sentence structure to help beginner Persian learners, especially those with Arabic language knowledge. This is a library research using linguistic approach and contrastive analysis to compare both sentence structre to predict difficulties that might appear in learning Persian. The differences of both languages, i.e. : 1) there ara two formulas of Arabic sentence structure: a) subject + predicate, and b) predicate + subject or predicate + subject + object. While in Persian the formula is subject + predicate or subject + object + predicate; 2) negative sentences of both languages use negative particle, but Arabic has various ones and most of them change the i‟rab; 3) Arabic passive sentences follows the wazn ل ِ ُع ف) past) and ُ ل ْع ف ُ يػ) present), while in Persian uses ending of شدن after the past verbs; 4) Arabic imperatives are formed by adding hamzah wasal replacing the huruf mudara‟ah, while in Persian by adding بــ before the root of present verbs; 5) fi‟l nahyi in Arabic are formed by adding lam an-nahiyah before majzum present verbs, while in Persian by adding نــ before root of present verbs.